2015
DOI: 10.1007/s10597-014-9792-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Community-Based Programs on Incarceration Outcomes Among Gay and Bisexual Stimulant-Using Homeless Adults

Abstract: This study was part of a randomized controlled trial designed to improve hepatitis knowledge and health promoting behaviors and subsequently decrease stimulant use and incarceration with 422 (G/B) homeless men between 18 to 46 years of age. Findings revealed that no significant program differences on incarceration in the four months following the intervention. However, younger participants (p = .010), and those with prior incarceration (p = .001) were at greater risk for incarceration at four months. An additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Nyamathi ( 2016 ) undertook an RCT to evaluate the impact of two interventions compared to usual care, an intensive peer coaching programme and the intensive peer coaching programme combined with intensive nurse case management. Although not described as such by the authors, the intervention appears to be ICM and has been treated as such for this review.…”
Section: Resultsmentioning
confidence: 99%
“…Nyamathi ( 2016 ) undertook an RCT to evaluate the impact of two interventions compared to usual care, an intensive peer coaching programme and the intensive peer coaching programme combined with intensive nurse case management. Although not described as such by the authors, the intervention appears to be ICM and has been treated as such for this review.…”
Section: Resultsmentioning
confidence: 99%
“…Another study found that economic hardship, prior incarceration, and substance use were associated with incident incarceration among young Black SMM and transgender women[ 20 ]. More research is needed on the relationship between incarceration and the re-entry needs among sexual and gender minorities, specifically employment, housing, and access to health care among Black SMM with a history of incarceration [ 14 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%